2021
DOI: 10.15835/nbha49412532
|View full text |Cite
|
Sign up to set email alerts
|

Continuous monocropping highly affect the composition and diversity of microbial communities in peanut (Arachis hypogaea L.)

Abstract: Continuous cropping systems are the leading cause of decreased soil biological environments in terms of unstable microbial population and diversity index. Nonetheless, their responses to consecutive peanut monocropping cycles have not been thoroughly investigated. In this study, the structure and abundance of microbial communities were characterized using pyrosequencing-based approach in peanut monocropping cycles for three consecutive years. The results showed that continuous peanut cultivation led to a subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Reports by FAO [21] and Mallano et al [22] showed that tilling agricultural lands constantly without rotations and fallows could erode farmlands, which could reduce soil fertility and crop yield. Most areas are associated with low crop yield and increasing production through opening of new farmlands has restricted potentials.…”
Section: Introductionmentioning
confidence: 99%
“…Reports by FAO [21] and Mallano et al [22] showed that tilling agricultural lands constantly without rotations and fallows could erode farmlands, which could reduce soil fertility and crop yield. Most areas are associated with low crop yield and increasing production through opening of new farmlands has restricted potentials.…”
Section: Introductionmentioning
confidence: 99%
“…Peanut ( Arachis hypogaea L.) is an important cash and oil crop in China, as well as a rich source of protein, vitamins, minerals and medicinal active ingredients such as flavonoids and phenolic compounds ( Li et al, 2021 ; Mallano et al, 2021 ). Due to the high economic benefit and limited planting area, peanuts are often intensively planted.…”
Section: Introductionmentioning
confidence: 99%
“…Maize ( Zea mays L.) is one of the three most important cereal crops, while peanut ( Arachis hypogaea L.) is the main oil crop and economic crop in the world. However, long-term continuous cropping has caused soil nutrient imbalance, serious soil erosion, bad seed quality and lower yield ( FAO, 2021b ; Mallano et al, 2021 ). Evidence indicates that intercropping with greater plant richness produces more roots, which contribute to the formation of soil aggregates; optimize the soil physical structure, which improves the soil chemistry parameters; and increase straw coverage, which decreases soil erosion ( Gamboa et al, 2020 ; Zhang et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…Rhizosphere soil microorganisms play an important role in crop growth and can be used as effective biological indicators of soil conditions ( Singh et al, 2009 ). It can clearly be seen that abnormal soil microflora is one of the main obstacles to continuous cropping ( Mallano et al, 2021 ; Song et al, 2016 ; Yuan et al, 2021 ). Numerous previous studies have confirmed that crop intercropping and rotation are an effective way to break the continuous cropping barrier and an important part of conservation agriculture ( Aschi et al, 2017 ; Hobbs, Sayre & Gupta, 2008 ).…”
Section: Introductionmentioning
confidence: 99%